Syntheses and characterization of the complexes of Molybdenum, Tungsten and Palladium with 2-diacetylpyridine-(1R)-(-)_fenchone azine - Mustaffa Ahmad (Tanjong Malim, 2010)
Syntheses and characterization of the complexes of Molybdenum, Tungsten and Palladium with 2-diacetylpyridine-(1R)-(-)_fenchone azine by Mustaffa Ahmad